1999
DOI: 10.1111/1475-4983.00073
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Eurasian fossil species of the bee Apis

Abstract: ABSTRACT. Fossil Apis species from the Oligocene, Miocene and Plio-Pleistocene of Eurasia are described and their relationships with Recent species are discussed. Several new populations of fossil bees are reported from the Oligocene and Miocene of France and Spain, including Apis aquisextusensis sp. nov. The present state of knowledge of fossil bee systematics is poor because of the general lack of preserved characters. Some of the problems, and items requiring further investigation, are identified. MAA (1953… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(40 citation statements)
references
References 15 publications
(30 reference statements)
0
40
0
Order By: Relevance
“…FWVA measurements of all examined specimens with well‐preserved forewings were subjected to a cluster analysis together with measurements of representative Recent specimens of honey bees from Germany ( A. mellifera ) and Asia ( A. florea , A. dorsata , A. cerana ). Additionally, Miocene and Oligocene specimens of honey bees from deposits that had sufficiently well‐preserved forewings were included to permit meaningful measurement and comparison (Cockerell, ; Théobald, ; Arillo et al ., ; Nel et al ., ; Wedmann, ; Engel, ; Engel et al ., ). We used FWVA measurements from Eocene Apidae, representing the genera Electrapis , Electrobombus , Succinapis , Thaumastobombus , Melikertes and Pygomelissa , along with other tribes of Recent corbiculate bees, as well as bumble bees ( Bombus , a Miocene and a present‐day species) and orchid bees ( Euglossa and Eufriesea ); and with representative non‐corbiculate Apinae ( Centris , Epicharis , Xeromelecta , Zacosmia ) as outgroup taxa because all these taxa provide a sufficiently rich venation to permit meaningful comparison.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…FWVA measurements of all examined specimens with well‐preserved forewings were subjected to a cluster analysis together with measurements of representative Recent specimens of honey bees from Germany ( A. mellifera ) and Asia ( A. florea , A. dorsata , A. cerana ). Additionally, Miocene and Oligocene specimens of honey bees from deposits that had sufficiently well‐preserved forewings were included to permit meaningful measurement and comparison (Cockerell, ; Théobald, ; Arillo et al ., ; Nel et al ., ; Wedmann, ; Engel, ; Engel et al ., ). We used FWVA measurements from Eocene Apidae, representing the genera Electrapis , Electrobombus , Succinapis , Thaumastobombus , Melikertes and Pygomelissa , along with other tribes of Recent corbiculate bees, as well as bumble bees ( Bombus , a Miocene and a present‐day species) and orchid bees ( Euglossa and Eufriesea ); and with representative non‐corbiculate Apinae ( Centris , Epicharis , Xeromelecta , Zacosmia ) as outgroup taxa because all these taxa provide a sufficiently rich venation to permit meaningful comparison.…”
Section: Methodsmentioning
confidence: 99%
“…This is a considerable oversight given that the fossil record demonstrates that past honey bee distributions were significantly different and included regions where they do not occur as natives today, such as North America (Engel et al ., ). The fossil record, revised extensively over the last 10 years, documents significant diversity of species and morphological varieties, particularly in the late Paleogene and early Neogene of Europe (Engel, ; Nel et al ., ; Ohl & Engel, ; Michez et al ., ). Indeed, phylogenetic investigations into the relationships among living and fossil honey bees indicate that basal species of Apis occur not in Asia, where the centre of modern diversity can be found, but instead within Europe.…”
Section: Introductionmentioning
confidence: 99%
“…Fossil honey bees are comparatively uncommon in Asia relative to the wealth of material available from a variety of European deposits of Oligocene and Miocene ages (e.g., Nel et al 1999; Kotthoff et al 2011, 2013). In fact, most fossil honey bees in Asia have been found at a single locality in Shandong Province (Zhang 1989; Zhang et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…All other fossil stingless bee species are rare, but span from the end of the Cretaceous (Maastrichtian) to Pleistocene copals (Michener 1982; Michener and Grimaldi 1988; Engel 2001b; Greco et al 2011; Engel and Michener 2013a, 2013b). Honey bees, again largely based on fossils of the worker caste, are known from a sparse number of deposits (Zeuner and Manning 1976; Nel et al 1999), but at some they can be found in large numbers (e.g., Armbruster 1938; Kotthoff et al 2011). These fossils span a range of ages from the earliest Oligocene through to the Pleistocene (Engel 1998a, 1999a, 2006; Engel et al 2009; Kotthoff et al 2011), although the taxonomic status of several putative species remains to be evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…If the dance did originate at the same time as Apis then it might have evolved in Europe, rather than in Asia. Fossils from Japan and the US suggest that different species of honey bee were present in many areas of the world during the Miocene (Nel et al, 1999;Engel, 2006;Engel et al, 2009;Kotthoff et al, 2011Kotthoff et al, , 2013, but a global cooling starting in Mid-Miocene (c. 15 million years ago) probably brought the demise of ancient honey bees in Europe, some parts of Asia and Northern America (Ruttner, 1988;Engel et al, 2009).…”
Section: Extinct Ancestorsmentioning
confidence: 99%